(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract: The investigation focused on synthesizing iron oxide (III) oxide nanoparticles (Fe3O4-NPs) using neem leaf extract, aiming for a straightforward and environmentally sustainable method. The synthesized nanoparticles showed distinct characteristics suitable for various applications, including antimicrobial and antifungal coatings. Transmission Electron Microscopy (TEM) confirmed the properties of the nanoparticles. Phytochemical screening revealed the presence of bioactive compounds in the synthesis process. The examination of antibacterial activity showed the effectiveness of Fe3O4 against microbial strains. This study lays the groundwork for environmentally sustainable antibacterial solutions with diverse applications.